Exploring gender disparities in the prosecution of theft cases: Propensity score matching on data from German court files - Leuschner, Fredericke (European journal of criminology, 2023)
This article engages in the discussion about gender disparities in prosecutorial decision-making. Appling propensity score matching after multiple imputation on data drawn from case files, the article examines differences in the prosecutorial treatment of male and female defendants in cases of minor theft in Germany. The matched data reveal significant differences between genders in the prosecutorial conclusion of proceedings: whereas dismissals because of other imposed sentences are more frequently imposed on male defendants, disposals with penalty fees are more common for female defendants. Hence, contrary to existing literature, the present study reveals harsher prosecutorial treatment of women because they have to pay penalty fees more frequently. The findings are contextualized with the focal concern hypothesis, which suggests that stereotypes influence decision-making in criminal proceedings. Together with the determination that women are more likely to pay fines or penalty fees completely and on time, this leads to the assumption that efficiency considerations by prosecutors influence their decision and make the imposition of penalty fees more attractive from an economic point of few.